MODELING OF TRAIN TRACK VIBRATIONS FOR MAINTENANCE PERSPECTIVES: APPLICATION - Tse Spartan Azoh; Wolfgang Nzie; Bonaventure Djeumako; Bertin Soh Fotsing (European Scientific Journal, ESJ, 2014)
The change of geometries, heterogeneities, degradation of components and the increase of maintenance cost of the railway track are due to the phenomenon of vibrations, which is the main problem of structural dynamic. The aim of this work is to propose a dynamic model for the prediction of rail vibrations during starting and steady state response. The DEM (Discret Elements Method) is adopted for the modeling of the vehicle. Thus components are assumed as rigid bodies mounted on series of springs and dampers with several degrees of freedoms. The rail road is discretized and modeled using FEM (Finite Elements Method). Rail-pad is modeled as a massless series of springs - dampers connected along the total contact area in between the rail and the mthsleepers. The sleepers are modeled as rigid elements connected by spring-damper. The ballast is modeled as separate vibrating mass connected by spring-damper coupled together vertically and horizontally while only the stiffness and damping effects of the subgrade is taken into account. The wheel-rail contact is modeled according to Herzian theory. Newmark time discretization and Newton Raphson iteration method have been used for models simulation in MATLAB. Displacements, velocities and accelerations of each modeled subsystem of components during starting and steady state response of the vehicle are calculated. The evolution of the wheel-rail contact load is also evaluated. Proactive maintenance actions are proposed in design.